Fungal Growth in Batch Culture – What We Could Benefit If We Start Looking Closer - Vrabl, Pamela; Schinagl, Christoph W.; Artmann, Desirée J.; Heiss, Benedikt; Burgstaller, Wolfgang (Frontiers in Microbiology, 2019)
Since filamentous fungi rapidly adjust their metabolic properties to environmental changes, a rigorous standardization and characterization of cultivation conditions is necessary to obtain meaningful and reproducible results. In batch cultures, which are commonly characterized according to the classical growth curve in textbooks (i.e., lag, exponential, stationary, and declining phase), this is of special difficulty. Although various studies in literature report atypically shaped growth curves of filamentous fungi in batch culture, systematic investigations on this topic are scarce and deviations are barely mentioned in textbooks. Summarizing approximately a decade of observations of growth characteristics from bioreactor batch grown filamentous fungi – in particular two strains (CBS123.823 and CBS123.824) of Penicillium ochrochloron – we demonstrate with a series of highly standardized bioreactor batch culture experiments that the classical growth curve failed to describe growth dynamics of the studied fungi in this work. The nature of the first exhausted nutrient was of remarkable importance for the resulting shape of the growth curve. In all experiments, online respirometry proved to be a powerful tool to distinguish growth phases and revealed more physiological states than expected from the mere biomass curve. In this respect we discuss why “atypical” shaped growth curves often remain unrecognized and that they might be the rule rather than the exception. Acknowledging the importance of the correct presentation of this complex topic in textbooks, we also propose a modified growth curve scheme to sensitize students for potential alternative shaped growth curves.